A salt-water reservoir as the source of a compositionally stratified plume on Enceladus - Postberg, Frank; Schmidt, J.; Hillier, Jon; Kempf, S.; Srama, R. (Nature, 2011)
Saturn's icy moon Enceladus is emitting a plume of water vapour and ice particles from warm fractures near its south pole known as tiger stripes. This plume material is thought to originate either from subsurface liquids or through the decomposition of ice. Postberg et al. report the first measurements of the compositions of freshly ejected particles, carried out by Cassini's dust detector during plume crossings. Salt-rich ice particles are found to dominate the total mass flux of ejected solids (>99%), which suggests that a salt-water reservoir with a large evaporating surface provides nearly all of the matter in the plume.
Gesehen am 11.05.2015